The Use of Web 2.0 Technology Tools and beyond in Enhancing Task Based Language Learning: A Case Study. - Nagaletchimee Annamalai (The English Teacher, 2019)
The study investigated the experience of 15 undergraduate students’ use of Web 2.0 tools and other relevant tools in completing their task for English language learning. The task involved students to work in small groups and carried out their task as an English language teacher. Students were given the task to prepare a grammar lesson by using Web 2.0 tools and other relevant tools. The data collection involved interviews and reflections. The emerging themes were analysed based on Braun and Clarke (2006) thematic analysis. The themes were categorized into positive and negative experiences. The findings indicated that students have utilised various type of Web 2.0 tools. In addition, students have used Web 2.0 as well as augmented reality to complete the given task. The study provides understanding to instructors that an effective learning environment needs to strike a balance between relevant technology tools and appropriate pedagogical practices to enhance student learning experience and to equip them with the twenty-first-century skills.